Pentingnya Multikultural dalam Lembaga Pendidikan - Melsya Firtikasari; Dinda Andiana (Nusa Putra University, 2023)
Multicultural education is a process of cultivating ways of life that respect, be sincere, and be tolerant of cultural diversity that lives in the midst of a plural society. Multiculturalism in principle is building oneself, the nation and the state without feeling as a burden and obstacle, but based on the bonds of unity, oneness and togetherness as well as mutual respect, respect, tolerance and cooperation in building an Indonesia that is advanced, safe, peaceful, peaceful, harmonious and prosperous. The importance of multicultural education in Indonesia is as an alternative means of conflict resolution, students are expected not to leave their cultural roots, and multicultural education is very relevant to use for the existing democracy as it is now. Multiculturalism in education that is developed has relevance to the Indonesian context, namely having the motto Bhinneka Tunggal Ika. This motto can accommodate proportionally, normatively and democratically for the Indonesian nation. Multicultural education is a very strategic and important issue to discuss because a nation is born from multiculturalism, so that the management of multicultural education or cultural diversity is a driving force for the development and goodness of a nation.